Research on new energy development comprehensive assessment model and application in China - Hu Jing; Huang Bibin; Du Dan; Wang Dan (E3S Web of Conferences, 2019)
In order to achieve the target of that non-fossil energy accounted for 15% in 2020 and 20% in 2030, new energy has developed rapidly in recent years in our country. However, the rapid development of new energy has brought many problems, such as the wind power curtailment, photovoltaic power curtailment, the unbalanced development in different regions and the imperfect policy. Therefore, it is necessary to make a comprehensive evaluation of the development of new energy, as the basis for the policy formulation and planning of new energy. In this paper, according to the characteristics of the new energy development in China, a comprehensive assessment model of new energy development is constructed, a set of assessment index system is proposed, which of the quantitative and qualitative combination, including energy production, energy consumption and policy mechanism from, and combining the Analytic Hierarchy Process(AHP) method to determine the weight coefficient. Finally, new energy development in Jiangsu province is taken as an example, the comprehensive evaluation of new energy development situation in 2018 is given.